TEKNIK COOPERATIVE LEARNING STRUCTURES UNTUK KETERAMPILAN MEMBACA BAHASA JERMAN PESERTA DIDIK SMA - OKTAVIAN PUJI SETYORINI, SHINTIA (LATERNE, 2017)
Based on the middle semester examination results of the students XI MIA 5 in SMAN 8 Surabaya showed that some participants scored less than 75 . The students got the score because they find the difficulty to understand the instructions and text content. Therefore, the new learning technique is needed, which fit with the student’s character and the materials. Cooperative Learning Structures could solve these problem. In Cooperative Learning Structures, the students learn together, a student will be a tutor, while others will be a tutee. After the first task was finished, they changes the role for the second task. This research as conducted to find out the results study on the reading comprehension using Cooperative Learning Structures. This problem of research is “how is the learning results of reading comprehension in eleventh grade by using Cooperative Learning Structures?” . this research has purpose to know the result of the reading comprehension. It used qualitative – descriptive research, and the data were collected through test results and questionnaires. The result shows that Cooperative Learning Structures technique helps the students to understand the texts. At the first meeting, the students got an average value of 74, it means that the  KKM has not reached. But the second meeting, they reached 83,3 , it means better than the first time. The third meeting got the students 89. The fourth meeting they reached 86. In the questionnaire, the students explained that Cooperative Learning Structures made them more interesting to learn Germany. From the research and the student’s answer in questionnaire , application of the learning technique can be summarized, that Cooperative Learning Structures technique can be applied to improve reading comprehension of the students. Keywords: Cooperative Learning Structures, the learning results, reading comprehension.